PENERAPAN METODE PENGAKUAN PENDAPATAN KONTRAK JANGKA PANJANG PADA PT. ADHIKARYA JAYA MANDIRI - Novianti, Merita Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research are: 1) to know the implementation of the recognition method for long term contract at PT Adhikarya Jaya Mandiri; 2) to know revenue the accuracy recognition and the burden on the projects which have been done then compare them with the theoretical aspect as the foundation. The data analysis technique is using descriptive which is qualitative. Based on the analysisi result and discussion can be concluded that 1): companyâs revenue recognition from the long term contract based on the physical progress is presented in project achievement reports which is created by the Site Engineering Manager (SEM) along with the field supervisors ; 2) there is significant difference in revenue recognition and profit in 2011 between the physical progress approach and the completion percentage method (cost-to-cost). The physical approach method recognize that the revenue and profit is higher by Rp. 13.836.974.074,- comparing with the cost-to-cost, therefore the revenue and profit presented in the financial report become over statement and inappropriate with the conservatism principle in the presentation of financial statement presentation; 3) the finishing percentage method (cost-to-cost) give the reasonable description in revenue recognition when comparing with the physical approach.Keywords: revenue, burden, and cost-to-cost.